Improving Lateral Series Addition Ability for Deaf Children Through Class VI Counting Funnel Media at SLB Kemala Bhayangkari - Wahyuni, Elsia Sri; Zulmiyetri, Zulmiyetri; Rahmatrisilvia, Rahmatrisilvia; Budi, Setia (Edumaspul: Jurnal Pendidikan, 2024)
This research aim to improved the abillity to add lateral series for deaf children at SLB Kemala Bhayangkari, Lintau Buo by using the educational media Funnel Counting. The counting funnel media acts as educational demonstration equipment that can be sen and make it easie for student to add up. The research use a quntitative approaach with ekperimental method, namelly Singel Subject Research(SSR) and Design A1-B-A2, and information is analysed using visuall graph by enter data in graphs wich are then anallyzed basd on condition A1-B-A2. The result of reseach using counted funnel mediacan improve the abillity to add lateral series for deaf children in class VI at SLB Kemala Bhayangkari, Lintau Buo.